2011
DOI: 10.1080/20445911.2011.521739
|View full text |Cite
|
Sign up to set email alerts
|

Differences in motor imagery times during aroused and relaxed conditions

Abstract: Motor imagery is recognized as an effective method used to enhance motor performance. However, several divergences remain in our understanding of the optimal physiological state required for effective imagery practice. In the present study, participants were required to use imagery in different states: aroused, relaxed, or in a baseline condition. The data revealed that imagery vividness did not differ in the aroused and relaxed condition. However, the ability to reach temporal equivalence between actual and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 30 publications
3
20
0
Order By: Relevance
“…During the MI sessions, the participants were sited with the legs extended to preserve physiological activation, favorable to MI efficiency (Holmes and Collins 2001). As suggested by Rushall and Lippman (1998) and Louis et al (2011), relaxation is not essential to MI training, and may even limit its benefits when the ultimate imagery outcome is to improve learning and motor performance. In other words, relaxation was only used during initial imagery sessions to help the participants to reduce interferences from distractions just before using MI, but they were then requested to increase their arousal level as they would do during physical performance (Guillot and Collet 2008;Louis et al 2011).…”
Section: Motor Imagery Trainingmentioning
confidence: 94%
See 1 more Smart Citation
“…During the MI sessions, the participants were sited with the legs extended to preserve physiological activation, favorable to MI efficiency (Holmes and Collins 2001). As suggested by Rushall and Lippman (1998) and Louis et al (2011), relaxation is not essential to MI training, and may even limit its benefits when the ultimate imagery outcome is to improve learning and motor performance. In other words, relaxation was only used during initial imagery sessions to help the participants to reduce interferences from distractions just before using MI, but they were then requested to increase their arousal level as they would do during physical performance (Guillot and Collet 2008;Louis et al 2011).…”
Section: Motor Imagery Trainingmentioning
confidence: 94%
“…As suggested by Rushall and Lippman (1998) and Louis et al (2011), relaxation is not essential to MI training, and may even limit its benefits when the ultimate imagery outcome is to improve learning and motor performance. In other words, relaxation was only used during initial imagery sessions to help the participants to reduce interferences from distractions just before using MI, but they were then requested to increase their arousal level as they would do during physical performance (Guillot and Collet 2008;Louis et al 2011). The participants were instructed to perceive muscle contractions and joint tension while imagining maximal isometric contraction of a full knee extension during 10 s, without moving.…”
Section: Motor Imagery Trainingmentioning
confidence: 94%
“…A negative difference between SC end and SC start would correspond to a decrease in arousal. This would mean that the athlete relaxed during the session, which could impair MI quality (16). The opposite result also is possible and would mean that the athlete increased his or her level of arousal.…”
Section: Mii: a Novel Hypothesismentioning
confidence: 96%
“…We investigated the effect of voluntarily changing imagery speed on complex motor tasks, as well as a highly automated motor task, for which the duration was set and controlled for many years (16). The data revealed that changes in MI speed modified the execution time of subsequent motor tasks.…”
Section: Chronometric Measuresmentioning
confidence: 99%
“…To explain, most studies that have used relaxation combined with imagery have not shown any significant benefits from the relaxation (Gray, Haring & Banks, 1984;Hamberger & Lohr, 1980;Weinberg, Seabourne, & Jackson, 1981) and many of the studies that have demonstrated strong imagery effects have not used relaxation procedures (Clark, 1960;Murphy, 1994;Smith & Holmes, 2004;Woolfolk, Parrish, & Murphy, 1985). In addition, recent research on the timing of motor imagery (see review by Guillot, Hoyek, Louis, & Collet, 2012) has shown that such timing was adversely affected when people performed motor imagery in a relaxed condition (see Louis , Collet, & Guillot, 2011). As Holmes and Collins (2001) pointed out, the idea of performing imagery in a relaxed state seems contradictory to what we know about the relatively high arousal states displayed by most athletes performing in competitive situations.…”
Section: Background To and Key Propositions Of The Pettlep Modelmentioning
confidence: 99%